ASSISTIVE TECHNOLOGY IN INCLUSIVE EDUCATION: ENHANCING ENGLISH LANGUAGE LEARNING FOR STUDENTS WITH SPECIAL NEEDS - Ergasheva Ozodabonu Bahodirjon qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This paper explores the role of assistive technology in enhancing English language learning among students with special needs within inclusive education settings. The study analyzes how various technological tools—ranging from text-to-speech applications to interactive digital platforms—facilitate language acquisition by promoting accessibility, engagement, and individualized instruction. The findings suggest that when used effectively, assistive technology significantly improves learning outcomes and empowers learners with special educational needs (SEN).